Analysis and Modeling of Anatomical Changes of the Anterior Segment of the Eye After Cataract Surgery with Consideration of Different Phenotypes of Eye Structure. (3rd October 2015) - Rękas, Marek; Barchan-Kucia, Kamilla; Konopińska, Joanna; Mariak, Zofia; Żarnowski, Tomasz
Abstract: Purpose : To study the relationship between phacoemulsification-related changes and the baseline parameters of the anterior chamber. Setting : Military Institute of Medicine, Warsaw, Medical University of Lublin, Medical University of Bialystok. Material and methods : The study included 228 patients. Anterior chamber depth (ACD), trabecular-iris angle (TIA), central lens thickness (CLT) and axial length of the eye (AXL) were determined prior to and 6 months after surgery. These measurements were used to calculate the ACDindex describing the degree of postoperative changes in the anterior chamber. K-means clustering, multiple regression and neural networks were used for the analysis. Results : Cataract surgery was reflected by changes in ACD and TIA. The character of changes was described by ACDindex ( p  < 0.05). Mean ACD0 was 2.51 ± 0.45 mm and increased to 3.84 ± 0.35 mm ( p  < 0.05), whereas mean TIA0 was 22.84 ± 7.43° and increased to 30.97 ± 7.99° ( p  < 0.05). ΔACD and ΔTIA were determined on the basis of baseline parameters defined by ACDindex, characterizing the structural type of the eye. The variability of ACDindex explained 42.65% of variance in ΔACD and ΔTIA. The quality of network for validation and test samples was from 0.72 to 0.83. Conclusions : Cataract surgery-related changes in ACD and TIA are determined by the type of the eye. Although the linear model of the relationship between baseline parameters of the eye and their postoperative changes is correct, it does not explain the degree of the latter phenomenon. Preoperative consideration of other parameters characterizing anatomical relationships of the eye would enable the prediction of phacoemulsification-related changes in the anterior segment.